تحليل الممشكلات الطلاب في ترجمة اللغة العربية إلى اللغة الإندونيسية في الصف الثامن للمدرسة الثانوية الحكومية 3 بنكا - Amalia, Siti; Munawwaroh, Ela Isnani; Yolensia, Viska (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
Translation is one of the important parts of students' Arabic learning because it has helped in the process of teaching. However, most students of the eighth grade of Islamic Junior High School Number 3 Bangka had difficulty in the process of translating from Arabic into Bahasa Indonesia. Students' translation problems impede the achieving of the educational goal. This study aimed to analyze students' problems in translating from Arabic into Bahasa Indonesia. The results of this study indicated two major problems: linguistic and non-linguistic. The linguistic problem found consisted of students' lack of proficiency in Arabic, students' lack of ability to learn Arabic grammar, students that tend to have difficulty arranging Arabic sentences to Bahasa Indonesia. The non-linguistic problems found consisted of students who were not interested in learning Arabic, students' ability to translate differently and the lack of time to learn Arabic and students still use google translation in the translation processes .